Embracing online distance learning software in the time of Movement Control Order (MCO) / Syarifah Adilah Mohamed Yusoff ... [et al.] - Mohamed Yusoff, Syarifah Adilah; Warris, Saiful Nizam; Johana Johan, Elly; Abdul Wahab, Naemah; Kadar, Rozita; Abu Bakar, Mohd Saifulnizam (Universiti Teknologi MARA, Kedah, 2022)
Online Distance Learning (ODL) is a kind of teaching and learning mode popular among part time students which usually committed with other priority job. In Malaysia, when MCO is firstly implemented, all level of education institutions has been plugged with ODL as the best mode in implementing teaching and learning for both full time and part time students in order to sustain the learning process. This research has collected information of online learning platform that frequently being used by bachelor degree students of Faculty of Civil Engineering, UiTM Cawangan Pulau Pinang who were enrolled in a Computer Programming Course. The data acquired at the start of the first three semesters of MCO were implemented. After the third semester of ODL implementation, MS Team was chosen as the most convenient online learning platform by students, with a 95% vote. This discovery is important for faculty and academic affairs to promote hands-on or additional training for lecturers and students to sharpen their skills using this popular software since the bright future of the ODL method for learning will be pursued and nourished even after the MCO.